Leader-expressed forgiveness and team performance: A two-paths model - Rego, A.; Valverde, C.; Oliveira, E.; Silard, A.; Pina e Cunha, M.; Sobral, F. (Human Performance, 2025)
As role models and salient sources of social information, forgiving leaders are prosocial facilitators of team interactions, with consequences for team performance. Through a multi-source field study (227 teams/leaders) and a vignette-based experiment (101 teams), we show that (a) leader-expressed forgiveness predicts team performance through, serially, team forgiveness climate and team helping behavior, and (b) this indirect effect is stronger when the strength (i.e. the consistency of expressed forgiveness across team members) of leader-expressed forgiveness and team forgiveness climate are high. Findings also show that (a) leader-expressed forgiveness predicts team performance through, serially, team psychological safety and team creativity, and (b) this indirect effect is stronger when the strength of leader-expressed forgiveness is high. Our findings suggest that forgiving leaders may play an important role as enactors of several team processes and emergent states that make teams more effective.